A haunting in Venice : a Hercule Poirot mystery - Christie, Agatha, 1890-1976 (William Marrow, an imprint of HarperCollins Publishers, 2023)
"At a Halloween party, Joyce--a surly thirteen-year-old--boasts that she once witnessed a murder. When no one believes her, she storms off home. But within hours her body is found, still in the house, drowned in an apple-bobbing tub. Famed detective Hercule Poirot is called in to investigate. Set against a night of trickery and the occult, it's up to Poirot to uncover the real evil presence responsible for this ghastly deed."--Amazon.